Three Trocars Laparoscopic Resection of Angiomyolipoma of the Liver - J. M. Ramia; R. De la Plaza; J. Quiñones; M. D. Sanchez-Tembleque; A. Caminoa; P. Veguillas; J. García Parreño (International Journal of Hepatology)
Angiomyolipoma of the liver (AML) is an infrequent neoplasm composed of three tissues (adipose, muscle and vessels). In spite of advances in radiology, preoperative correct diagnosis is difficult. Clasically, a conservative management strategy was adopted in patients with asymptomatic tumors less than 5 cm with undoubtful diagnosis. But after publishing some few cases of malignant angiomyolipoma a more radical has been advocated. Laparoscopic resection of liver tumors is becoming a excellent approach for operating on benign liver tumors. Usually is performed using five trocars but in some cases a less invasive technique with three trocars could be used. We present a laparoscopic resection of liver angiomyolipoma in a 65 year-old male using only three trocars and also discuss the optimal management of AML and technical tips of three-trocar technique.